First aid health education interventions in the school environment: an integrative review - Bianco da Cruz, Karine (2020)
Objective: to identify in the literature which health education interventions in first aid are used in the school setting. Method: This is a descriptive study, as an integrated review of the literature, with a search performed in the LILACS, BDENF, MEDLINE and PubMed platforms, selecting articles published between 2009 and 2019, in Portuguese, English and Spanish, available for free and complete access, which characterized original intervention studies in schools with the theme of first aid. Result: We found 1937 articles which, after analyzing the inclusion and exclusion criteria, resulted in 15 articles in the final sample. The articles were divided into two discussion categories: first aid education actions for teachers and employees and first aid education actions for students. Conclusion: Collaborators, teachers and students are not prepared to provide first aid in schools, and that teaching first aid, using different methodologies, significantly improves people's knowledge and skills in this context. These studies justify the need to promote health education in schools about first aid.